O bõõ pagão : a cavalaria de Palamedes em A demanda do Santo Graal - Zaban, Thalles Tadeu Brunello (2013)
Presumably translated to Portuguese in the 13th century, from a French manuscript, lost nowadays, A demanda do Santo Graal broaches the matter of Britain by a pronouncedly religious view, and aims, as an exemplum, to serve as a tool for the configuration of a pretense Christian moral values code within the Knighthood. On this matter, Palamedes deserves distinction among the novel characters for being the only pagan knight in activity admired by the king’s Arthur Christian courtisans. Considering the Catholic church (pre)domination regarding the political, cultural and ideological spheres when the novel was written, the exaltation of the moor Palamedes moral and martial qualities gains special importance, once it represents, in the Demanda’s ambivalent valuing structure – in which worldly and courtisan values oppose the Christian exemplar behavior –, the order of chivalry constitutive atributes excelency, despite its submission to the Church. Thereby, collating the Christian and Arabian knighthoods, considering the constitutive discourse of the late Middle Ages chivalric narratives and remarking the Moorish East representation on the Iberian Peninsula’s imaginary, this work analises the character’s function on the novel’s structure, examining the orientation of the episodes that forms its deeds. And then we discover a character that, something alien to etnic and cultural conformations but inside the courtly universe of expectations marked by the sign of ambiguity, excels as a knight.